Pemanfaatan Bahasa Daerah Sebagai Mediator Dalam Pembelajaran Agama Katolik Bagi Siswa SD YPPK Santo Samuel Mokbiran Kabupaten Boven Digoel Papua Selatan - Yunarti, Berlinda S.; Kanyek, Elisabeth (Sekolah Tinggi Katolik Santo Yakobus Merauke, 2024)
This research aimed to analyze the use of local language as the language of instruction in teaching Catholic Religious Subject at YPPK St. Samuel Mokbiran Elementary School, Boven Digoel Regency, South Papua Province. This research was motivated by the students' low mastery of the Indonesian language and the students' better mastery of the local language Muyu Kawiyet. Qualitative research methods were employed to collect data through observation and interviews. The research results showed that the use of the local language as the language of instruction in the learning process assisted the students to better understand the learning materials, especially the main prayers of the Catholic Religion. However, this also hindered their mastery of Indonesian, thereby impacting their overall academic development. To address this issue, this study suggested the use of bilingual approach and the provision of more adequate learning facilities.